REMOTELY OPERATED VEHICLE (ROV) PROTOTYPE - MOHAMAD, MARTINA MUHAIZIRA BINTI (Universiti Teknologi PETRONAS, 2012)
This paper describes the Remotely Operated Vehicle (ROV) prototype where the objectives are to study and theoretically design the prototype for Final Year Project (FYP). This dissertation starts with the introduction of the whole idea of the project, followed by the objectives to be achieved, literature review, methodology, and lastly results and discussions. The scopes of ROV are first discussed based on the current international applications, then focused down to Southeast Asia region and lastly, the ROV applications in Malaysia. Generally, the work class ROV (Class III) is the most famous ROV which currently being applied in the industry. However, the work class ROV is big in size and came up with complex control. Thus, a ROV prototype is done as a project that will be able to provide one alternative which can be further expanded in terms of its functions into smaller and easier tasks that can be carried, such as for educational purposes and fishery industries. Few steps are taken to ensure the successful of the prototype. The theoretical studies are made to ensure that basic understandings of the working of each basic part of ROV that includes lighting, propulsion, buoyancy, camera and its frame shape are obtained. Based on theoretical studies, designs and simulations made, all designs of each part are constructed into real circuits or prototype The ROV prototype is designed with the most simple, reliable and also importantly to meet the budgeted cost. The ROV prototype is also designed to ensure that its subsystem is compatible with each other. As example, the creation of the frame is planned to be constructed by using suitable material, which is combined together to form the rectangle shape the frame. The same method applied to the other parts of ROV. Lastly, after all the constructions are done, the prototype is being tested and modified accordingly to ensure that it can work safely. Trough out the project, it is observed that a simple ROV can be made to carry stated simple tasks. The project is considered success however more underwater tests should be done to the prototype because a lot of enhancements especially on the buoyancy and propulsion system can still be modified.